Prevalence of Work-Related Musculoskeletal Disorders Among Tire Workshop Mechanics in Pagoh, Malaysia - Nasarudin, Muhammad Aisar; Mustafa El Bakri , Dr. Helmy (Progress in Engineering Application and Technology, 2022)
The risk of MSD disorders is pain that occurs in joints, muscles, tendons, ligaments, nerves, discs, blood vessels, and soft tissues. Most vehicle mechanics are often exposed to the risk of MSD disorders in the workplace due to ergonomic body posture while doing any type of job. This study aims to conduct an ergonomic assessment of the common posture of workers in tire shops using NMQ, REBA, and RULA assessments. The study was conducted at Chensing Tires World Sdn. Bhd. located in the area around Pagoh, Johor. This method uses a 3D Scanner, Geomagic for Solidworks, and Catia V5R21 to be scanned and edited for inclusion in engineering software. The results of the study found that the five actual postural conditions that are often performed by tire mechanics are the worst postures that invite the risk of MSD disorders in the workplace. A comparison through manual RULA analysis with RULA in Catia found that the risk of MSD disorders is easily exposed to the neck, trunk, upper arm, lower arm, wrist, and leg area of ​​tire mechanic workers. The RULA analysis performed in Catia is the most accurate and in-depth assessment to determine the level of postural risk including the load imposed on each limb of a vehicle tire mechanic.